2019
DOI: 10.1017/s2045796019000271
|View full text |Cite
|
Sign up to set email alerts
|

Disentangle the neural correlates of attachment style in healthy individuals

Abstract: Since its development and theorisation in the 60s, attachment theory has greatly influenced both clinical and developmental psychology suggesting the existence of complex dynamics based on the relationship between an infant and its caregiver, that affects personality traits and interpersonal relationships in adulthood. Many studies have been conducted to explore the association between attachment styles and psychosocial functioning and mental health. By contrast, only a few studies have investigated the neurob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The connectivity differences between the two groups mostly represented different roles of the striatum in socio-emotional information processing. These findings correspond to adult attachment studies which showed that the fronto-striatal-limbic circuit function is modulated by attachment type during the processing of social and attachment-related cues ( Perlini et al, 2019 ). In particular, this circuit is responsible for modulating affective evaluations and often represents an access to memory about previous experiences, thinking of negative emotions or stress responses ( Coan, 2010 ; Vrtička and Vuilleumier, 2012 ; Williams et al, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…The connectivity differences between the two groups mostly represented different roles of the striatum in socio-emotional information processing. These findings correspond to adult attachment studies which showed that the fronto-striatal-limbic circuit function is modulated by attachment type during the processing of social and attachment-related cues ( Perlini et al, 2019 ). In particular, this circuit is responsible for modulating affective evaluations and often represents an access to memory about previous experiences, thinking of negative emotions or stress responses ( Coan, 2010 ; Vrtička and Vuilleumier, 2012 ; Williams et al, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…In conclusion, we propose that in addition to OFC even the specific cerebellar areas previously demonstrated to be involved in emotional regulation have to be included in the current neurobiological models of human attachment 85 . The present research may represent a step forward in mapping out the attachment process and improving our understanding of the pathophysiology of the attachment-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we propose that in addition to OFC even the speci c cerebellar areas previously demonstrated to be involved in emotional regulation have to be included in the current neurobiological models of human attachment 75 . The present research may represent a step forward in mapping out the attachment process and improving our understanding of the pathophysiology of the attachment-related disorders.…”
Section: Discussionmentioning
confidence: 99%